IMPROVING STUDENTS' LEARNING OUTCOMES THROUGH THE APPLICATION OF THE PROBLEM BASED LEARNING MODEL IN THE CULTURE OF ARAB SOCIETY BEFORE ISLAM AT MAS RUSIP - Juraini (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
In essence, education is carried out from an early age to college. Educating is not the main task of parents. However, not all educational tasks can be carried out by parents in the family, it takes encouragement and assistance from a teacher for formal education. However, sometimes, there are some teachers who carry out the learning process whose implementation uses the lecture method so that it seems boring to the material presented. The purpose of this study was to determine the increase in student learning outcomes after the application of the Problem Based Learning (PBL) model in SKI learning and to identify the obstacles faced in the learning process. This type of research is Classroom Action Research (CAR) with the aim of improving the quality of learning. This study consists of two cycles. Based on the results of the study, it was found that there was an increase in student learning achievement and student enthusiasm in participating in learning.